Stakeholders' Observed Impact of the Adopt-an-Estero Water Body Program in Segment 3 of Iloilo Batiano River, Philippines - Shirley Hampac; Belinda Gavadan (Philippine Association of Institutions for Research, Inc., 2022)
Cleaning a river needs the collaboration of all stakeholders. Thus, this study delved into the stakeholders' observed impacts of the Adopt-an-Estero Water Body Program (AEWBP) jointly implemented at Segment 3 of Batiano River by the JBLFMU-Arevalo, DENR 6, and other sectoral groups. The study employed a descriptive research design with ninety-two respondents identified through purposive sampling. The findings revealed that the majority participated once to five times in the cleanup. When not involved in cleanup activity, stakeholders visited the area five or more times a year. The observed impacts of AEWBP on the community include environmental education, increased health and safety, and established community relationships. On stakeholders, the observed impacts were becoming more environment-aware, motivated to reduce and properly dispose of garbage, and disciplined. On the environment, respondents observed healthier aquatic status, reduced plastic, and increased environmental awareness. Current strategies used, like the length of cleanup, using gaff, and the type of people involved, was rated highly effective, where a significant difference was noted in the stakeholders' observed effectiveness. The stakeholders cited other effective ways of implementation like more often clean up, dredging the river, more funds, continuing education, and more organizations. This study concludes that the AEWBP is a good learning avenue for the environmental protection of the community.